A novel redshift mechanism of Ce3+ emission in ZrO2-Ce: YAG composite phosphor ceramics. Issue 15 (December 2020) - Chen, Jie; Tang, Yanru; Yi, Xuezhuan; Tian, Yanna; Zhao, Di; Lin, Hui; Zhou, Shengming
Abstract: In this work, ZrO2 -Ce: YAG composite phosphor ceramic for the application of high brightness w-LEDs was fabricated for the first time. A novel redshift mechanism of Ce 3+ emission is discovered in the composite ceramics that the oxygen vacancy introduced into YAG lattice by the high-temperature reduction of Zr 4+ can cause a remarkable non-radiative transition of excited electrons and produce a large redshift from 540 nm to 570 ∼ 610 nm. This kind of redshift has provided a new approach to the supplement of the red component in Ce 3+ emission spectra beyond the regular ways of larger rare-earth ions doping or M 2+ -N 4+ double substitution.